2019
DOI: 10.1186/s13011-019-0242-1
|View full text |Cite
|
Sign up to set email alerts
|

Application of data mining techniques and logistic regression to model drug use transition to injection: a case study in drug use treatment centers in Kermanshah Province, Iran

Abstract: BackgroundDrug injection has been increasing over the past decades all over the world. Hepatitis B and C viruses (HBV and HCV) are two common infections among people who inject drugs (PWID) and more than 60% of new human immunodeficiency virus (HIV) cases are PWID. Thus, investigating risk factors associated with drug use transition to injection is essential and was the aim of this research.MethodsWe used a database from drug use treatment centers in Kermanshah Province (Iran) in 2013 that included 2098 record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Other studies showed that the machine learning methods performed as good as the LR [ 10 ], which is in agreement with our results. However, other studies indicated machine learning methods of SVM, NN and DT outperformed logistic regression in terms of prediction performance [ 10 , 11 , 14 , 23 ]. In those studies, there were imbalanced data such that a large proportion of the samples did not experience the event of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that the machine learning methods performed as good as the LR [ 10 ], which is in agreement with our results. However, other studies indicated machine learning methods of SVM, NN and DT outperformed logistic regression in terms of prediction performance [ 10 , 11 , 14 , 23 ]. In those studies, there were imbalanced data such that a large proportion of the samples did not experience the event of interest.…”
Section: Discussionmentioning
confidence: 99%
“…We applied a tenfold cross-validation strategy to tune the hyper-parameters of the used models over the training set. Finally, for the trained model with the best performance over the test set, the most important variables in predicting the positive WTP and WTA were determined separately using the variable importance index [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, machine learning (ML), an important branch of artificial intelligence, has been widely used in many fields. In particular, breakthroughs have been made with ML methods in medical diagnosis and outcome prediction [ 8 , 9 ]. These methods are generally categorized into supervised or unsupervised learning.…”
Section: Introductionmentioning
confidence: 99%